Catalysis with microporous aluminophosphates and silicoaluminophosphates containing transition metals - Hartmann, Martin; Elangovan, S. (Elsevier, 2010)
The literature related to the catalytic activity of aluminophosphate (AlPO) and silicoaluminophosphate (SAPO) molecular sieves containing transition metal ions and/or transition metal clusters is reviewed. Microporous crystalline metal aluminophosphates (MeAPOs) and metal silicoaluminophosphates (MeAPSOs) represent an important group of inorganic materials because of their large potential as adsorbents and catalysts. This review focuses mainly on the catalytic activity of MeAPOs and MeAPSOs in comparison with the corresponding MeAPSOs covering the literature through 2008. The catalysis over these materials is summarized and discussed with respect to the catalytic performance, possible reaction mechanisms, and potential applications. © 2009 Elsevier B.V.